Revised Reliable Algorithm with Results & Algorithm for Thinning Numeral Pattern (International Journal of Engineering and Computer Science, 2014)
thinning algorithms have played an important role in the preprocessing phase of OCR systems.. Many algorithms for vectorization by thinning have been devised and applied to a great variety of pictures and drawings for data compression, pattern recognition and raster-to-vector conversion. The vectorization algorithms often used in pattern recognition tasks also require one-pixel-wide lines as input. But parallel thinning algorithms which generate one-pixel-wide thinnings can have difficulty in  preserving the connectivity of an image or generate spurious branches. A few most common thinning algorithms have been implemented and evaluated on the basis of performance parameters.